“Always an Imam”: Understanding the Occupation of Imam from Theoretical Perspectives on Professions - Trucco, Noemi (Religions, 2024)
In this article, the occupation of the imam is analysed using a profession-theoretical approach. Following Oevermann, we view professionalised action as a relational practice, characterised by a paradoxical unity of diffuseness and specificity. Drawing on empirical data on imams in Switzerland, we highlight several factors that contribute to a shift towards more diffuse social relationships between professionals and their clients: task-specific boundaries become blurred, and temporal and spatial limits break down. These factors help to explain why imams in Switzerland report feeling stressed and overburdened. We argue that the role of the imam can, in principle, be conceptualised as a profession. From the perspective of a power approach to professions, however, the concept of profession can only be applied to the occupation of an imam to a limited extent, as it is not universal, but remains reserved for men.